Audiovisual Translation as a Media for Teaching EFL Vocabulary to Primary School Students in Indonesia - Kembaren, Farida Repelita Waty; Rajagukguk, Sahmiral Amri; Pratiwi, Anggun Siska; Khairani, Khairani (Institut Agama Islam Negeri Ponorogo, 2024)
This research demonstrates the important role of technology in education by highlighting the potential of audiovisual techniques as learning media for primary school students. Previous research studies have shown that appropriate audiovisual presentations can improve comprehension, especially in today's children who are enthusiastic about multimedia technology. A qualitative research method using a classroom action research design was used to carry out the research procedure, while thematic analysis was used to analyse the data and evaluate the findings. The aim of this study is to evaluate one of the most effective EFL vocabulary teaching methods for primary school students, namely audiovisual translation, and to summarise the students' impressions while learning vocabulary using audiovisual translation. This research contributes to innovative EFL teaching methods by suggesting the widespread use of audiovisual translation in primary schools around the world, especially in Indonesia, based on its proven success and positive responses from students.